Concepts of education management - Santosh Kumar Yadav (Ane books, 2018)
The present book is the essential literature for the person associated to education system at any level. As a systematic approach this book can be used by teaching / non-teaching / administration section of educational institutions. The students of B.Ed., M.Ed. and Research will find the book most fruitful.